New Challenges of the Information Content in Ukraine - H. HOLUBOVA (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2020)
The author examines the historical background regarding the formation and development of the information services market as a major catalyst for the development of the information society. The level of development of information activity in the leading countries of the world is the result of a long historical process of evolutionary and revolutionary transformations.